Encyclopedia of Hispanic American literature - Ramirez, Luz Elena (Facts on File library of American literature, 2008)
Covers Hispanic-American authors and works that are historically significant or gaining a reputation in today's literary circles. Authors include Isabel Allende, Julia Alvarez, Pat Mora and more.